2022
DOI: 10.1029/2022jd036785
|View full text |Cite
|
Sign up to set email alerts
|

Active Layer Thickness in the Northern Hemisphere: Changes From 2000 to 2018 and Future Simulations

Abstract: Permafrost is a product of cold climates and is mainly distributed in cold climatic high latitudes and high elevations in the Northern Hemisphere (Zhang et al., 1999). The permafrost regions account for approximately 22% of the land area in the Northern Hemisphere (Obu et al., 2019). Permafrost degradation may lead to greenhouse gas emissions from the decomposition of organic carbon stored in the permafrost regions, further contributing to global warming and accelerating permafrost thaw (Schuur et al., 2015).T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…The dataset therefore provides a comprehensive view of landscape level spatial and temporal patterns of ALT over the NPR that corresponds closely with in situ ground measurements of ALT represented from the sparse station network. Our results suggest that there are widespread deepening trends of ALT, similar to previous analyses (Park et al 2016, Peng et al 2018, Li et al 2022a, 2022b. Furthermore, the deepening ALT is broadly aligned with increases in permafrost temperature (Biskaborn et al 2019).…”
Section: Comparison With Other Datasetssupporting
confidence: 88%
See 1 more Smart Citation
“…The dataset therefore provides a comprehensive view of landscape level spatial and temporal patterns of ALT over the NPR that corresponds closely with in situ ground measurements of ALT represented from the sparse station network. Our results suggest that there are widespread deepening trends of ALT, similar to previous analyses (Park et al 2016, Peng et al 2018, Li et al 2022a, 2022b. Furthermore, the deepening ALT is broadly aligned with increases in permafrost temperature (Biskaborn et al 2019).…”
Section: Comparison With Other Datasetssupporting
confidence: 88%
“…Li et al (2022b) used the Kudryavtsev method and integrated various forcing data (such as temperature, snow, vegetation and soil data) to simulate changes in ALT in the NPR and found ALT increased at a linear rate of 0.86 cm yr −1 from 1969 to 2018, with the highest thickening rate in Alaska and the Mongolian Plateau (∼2.4 cm yr −1 ) and the lowest thickening rate in Greenland (∼0.3 cm yr −1 ). Li et al (2022a) reported an overall significant linear increase in ALT of 0.65 cm yr −1 , with approximately 71% of the NPR showing an increase from 2000 to 2018. These studies provide useful understanding of broad regional patterns and climate impacts on ALT trends, but are generally too coarse to resolve finer landscape heterogeneity, where local terrain, soil, and vegetation features may have a larger influence on permafrost stability.…”
Section: Introductionmentioning
confidence: 97%
“…Rapid climatic warming has increased the mean annual air temperature (MAAT) in Alaska by 2.1 • C over the last 70 years (Walsh and Brettschneider 2019), which has altered hydrologic conditions via reduced snowpack, permafrost degradation (Li et al 2022), increased subsurface flow and soil moisture (Walvoord et al 2012), and altered precipitation (Bieniek et al 2014). These hydrologic responses to anthropogenic climate change are often reflected by the magnitude and seasonality of river discharge (Van Vliet et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Permafrost has been considered to be an important indicator of moderate climate change because it is sensitive to the air temperatures and precipitation (Farquharson et al., 2019; Mekonnen et al., 2021). Recently, the degradation of permafrost has received considerable attention (Li et al., 2022; Ran et al., 2018; Xia et al., 2022). Previous studies indicate that modern climate change has triggered numerous retrogressive thaw slumps (RTSs) in permafrost landscapes, especially during the thaw season in years with higher air temperatures and precipitation (Lewkowicz & Way, 2019; Luo et al., 2022b).…”
Section: Introductionmentioning
confidence: 99%